If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7h + -29 = 34 Reorder the terms: -29 + 7h = 34 Solving -29 + 7h = 34 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 7h = 34 + 29 Combine like terms: -29 + 29 = 0 0 + 7h = 34 + 29 7h = 34 + 29 Combine like terms: 34 + 29 = 63 7h = 63 Divide each side by '7'. h = 9 Simplifying h = 9
| z^3+2*z^2-7*z=-4 | | 7m+4=53 | | 602-6X=2.5 | | 2(b-6)=5b-30 | | 25y+8=13 | | 9h+4=85 | | a*6-25=125 | | 10h+6=74 | | 9h+4=74 | | 7m-13=57 | | 6x^2-6x-12x=0 | | (x+4)*((x^2)-3x+2)*5=5*(x+4) | | (z+4)*((z^2)-3z+2)*5=5*(z+4) | | 2b+2d=b+2d*1.414 | | 2.83+2d=b+2d | | 20y^2-12x-6x^2+y^5=0 | | 13200-250S=10560 | | 13200-250S=2 | | x+x-1=61 | | 4x+8=4(x-1) | | x^5+x^3+6x-13=0 | | P=10x-(4.5x+90) | | 6x+15=20-5x | | 3(8m+5)=39 | | 16+4*(7+8)-3= | | 5+5=50 | | 0.2y+8=0.3y-5 | | 0.2y+8=0.2y-5 | | 4x(2+6x)= | | 11x+2y=4y+x | | -9x-7=2x+15 | | 10x+2y=4y+x |